I understand Lemma 8 in Chapter 1 from Lehmann's Testing Statistical Hypotheses [or Lemma 2.7.2 in Lehmann and Romano] as follows:

If the pdf of an exponential family is $$p_{\theta}(x)=\exp\bigg\{\big(\eta_1^\top(\theta),\eta_2^\top(\theta)\big)\big(T_1(x),T_2(x)\big)^\top-\xi(\theta)\bigg\}h(x),$$ then the pdf of $T_1$ is presumably $$g_{\theta}(t)=\exp\{\eta_1^\top(\theta)t-\xi(\theta)\}.$$ However, when I take the joint distribution of $n$ iid rv's form normal distribution $N(\mu, \sigma^2)$ as an example, where $$\eta(\theta)= \left( \frac{\mu}{2\sigma^2},\frac{1}{2\sigma^2} \right)^\top, T(x)= \left( \sum_{k=1}^n X_k,-\sum_{k=1}^n X_k^2 \right)^\top,\xi(\theta)=\frac{n\mu^2}{2\sigma^2}+\frac{n}{2}\log\sigma^2,h(x)=(2\pi)^{-\frac{n}{2}}$$ The lemma yields that the pdf of $T_1=\sum_{k=1}^n X_k$ should be

\begin{align} g_\theta(t) & =\exp\left\{\frac{\mu}{\sigma^2}t-\frac{n\mu^2}{2\sigma^2}-\frac{n}{2}\log\sigma^2\right\} \\[6pt] & = \exp\left\{-\frac{(t-\mu)^2}{2n\sigma^2}+\frac{t^2}{2n\sigma^2}-\frac{n}{2}\log\sigma^2\right\} \end{align}

Whereas, since $X_k$'s are iid normal distributions, their sum should also be a normal distribution with mean $n\mu$ and variance $n\sigma^2$, that is:$$g_\theta(t)=\exp\left\{-\frac{(t-\mu)^2}{2n\sigma^2}-\frac{1}{2} \log(n\pi\sigma^2)\right\}$$ Why do the two results contradict? Did I misunderstand the lemma?enter image description here

  • 1
    $\begingroup$ As @Sextus answered below, if you read the lemma more carefully, you would find it asserted the form of the joint distribution of $(T_1, \ldots, T_s)$, rather than asserting the marginal distribution of $T_1$ alone. So you applied the lemma incorrectly. $\endgroup$
    – Zhanxiong
    May 21, 2023 at 14:23

1 Answer 1


The lemma states that that you can express the probability in that way with respect to a specific measure.

You do not have

$$dP(t)=\exp\{\eta_1^\top(\theta)t-\xi(\theta)\} \, d t$$

but instead you need to use

$$dP(t)=\exp\{\eta_1^\top(\theta)t-\xi(\theta)\} \, d \nu_\theta( t)$$

when you use $\nu(t) = \int e^{-ct^2} \, dt = \frac{\sqrt{\pi} \operatorname{erf}(\sqrt{c}t)}{2\sqrt{c}} $ then $d \nu_\theta( t) = e^{-ct^2} \, dt$ and

$$dP(t)=\exp\{\eta_1^\top(\theta)t-ct^2-\xi(\theta)\} \,dt$$

You will have to figure out the constant $c$ but in this way you have a form that relates to the normal distribution.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.